A (des)proteção do trabalhador no sistema prisional: da seletividade penal às impossibilidades da ressocialização - Pinheiro, Nataly de Sousa (2022)
This thesis has as its object of research the prison labor in order to understand it as an intrinsic category to the capitalist mode of production, which in this sen particularities and peculiarities especially when it is central in the process of social reintegration of the person deprived of liberty. Following this line, the social structure maintains the black and poor population as a privileged target of State surveillance, control and violence. The criminal selectivity permeates the constitution of criminal policy in Brazil, interconnected by socio-historical determinants that lead a certain portion of the population to this institution called prison. In contemporary capitalism, the policy of criminal enforcement presents itself as a contradiction since the isolation imposed by the penal sanction makes reintegration difficult due to the prisoner's lack of social interaction. Such arguments instigate the problem of our proposal, as we question whether the legislation that deals with the work of people who are serving a sentence is embodied in an instrument for the process of resocialization and reintegration into society or ends up making living conditions even more precarious of those who are deprived of their liberty, given the gaps in the legal normative that deal with prison labor. The hypothesis is that legal regulation for workers working in prison is incipient, which increases the differences between prisoner workers and "free" workers, making prison labor becomes useful and necessary for the capitalist mode of production as it is at the same time an instrument of control and exploitation of a certain portion of the population. The normative incipience is embodied in a serious violation of rights contributing to the precariousness of the living conditions of prison workers. In this sense, the research proposal has the general objective of analyzing the functionality of prison labor for the capitalist mode of production, understanding whether the regulations of the Brazilian legal system which deal with the work performed by inmates contribute to their social reintegration, whatever the regime they are inserted. Methodologically, the category of totality refers to the entire research. Therefore, bibliographic research was carried out among the academic production that already analyzes this theme and, on another hand, it was sought to know the theme from research with secondary data about the object of study, obtained through research carried out previously. As well as with the collection and analysis of information and data related to prison work which were requested from the competent bodies based on the Law on Access to Information. With this, we try to articulate the theory-practice unity. Thus, the research can be characterized as being exploratory and descriptive. With this, we identified that the existing legal apparatus on prison labor legitimizes the exploitation of those considered unnecessary to the capitalist mode of production who are in a situation of deprivation of liberty. Empirically, the abandonment of the human condition of these disposables" in prison is perceptible, under the discourse of a supposed resocialization are expropriated in favor of the development of capital itself which takes advantage of all spaces to guarantee the conditions for its reproduction, even if this implies instituting a true social barbarism.